Management and Public Investment in the Peruvian Army in the Face of Disasters caused by the El Niño Phenomenon in Northern Peru - Roger, Balcázar Zárate, Williams; Yulsi, Salas Saavedra de Laura; Alberto, Carlín-Marres, Luis (Migration Letters, 2024)
The Peruvian military has been instrumental in responding to the disasters caused by the El Niño phenomenon in northern Peru. The government’s public investment in disaster preparedness and response has also been critical in ensuring that the military is well-equipped and trained to handle such emergencies. Effective management strategies have further enhanced the army’s ability to respond promptly and effectively to disasters. The government’s public investment in disaster preparedness and response has also been critical in ensuring that the military is well-equipped and trained to handle such emergencies. The population was made up of 100 workers from different social fields, such as meteorological engineers, construction workers and residents of the affected areas, having a sample of 40 participants in which it was chosen for the convenience of the author. After this process, the reliability of the instrument was carried out through a pilot test, the data obtained were analyzed using Cronbach’s alpha statistical test, resulting in the value of 0.91 indicating that the instrument is on the scale of excellent reliability. Statistics were produced to help verify the research.